COVID-19: Remote education for the development of research competencies in undergraduate students - Bustillos-Cotrado, Jose Antonio (2023)
During the health emergency generated by the coronavirus (COVID-19), the education sector had the need to adapt to remote to adapt to remote education in order to continue with the teaching-learning process in terms of pedagogical practices, teaching strategies, etc.teaching-learning process in pedagogical practices, didactic strategies, etc. In this context, the scientific production of universities and much less the research training of students, and the search for new alternatives in their learning should be promoted. the search for new alternatives in their learning (Ocampo-Eyzaguirre et al., 2021). In this regard, this the results of a study on the didactic strategies and research skills in students of the diploma course in and research skills in students of the diploma course in research teaching carried out through modules in the Microsoft Teams Microsoft Teams platform in a Peruvian public university.